Kesantunan Linguistik dalam Interaksi Jual Beli di Pasar Raya Solok - Mayang Sari Anugrah; Ike Revita; Rina Marnita (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This research was conducted to describe the linguistic politeness of buyers in Pasar Raya Solok. This study is focused on discussing the politeness forms and the politeness functions of buyers in Pasar Raya Solok. This research includes three stages, namely collecting the data, analyzing the data, and presenting the data analysis. Data is collected by the listening method. The technique used is the recording technique, note-taking technique, and interview. Data were analyzed using translational and pragmatic methods. The results of data analysis are presented using formal and informal methods. The results of the analysis found politeness forms, forms of politeness in asking, forms of politeness in rejecting, forms of politeness in asking questions, forms of politeness in commanding, forms of politeness in promising, forms of politeness in praising, and forms of politeness in giving. The author also found politeness functions consisting of competitive functions and pleasant functions. The politeness forms are used by the buyers as the manner in which the buyer buys goods in the market so that the language is polite. The politeness function used by the buyers can be formulated as a competitive function and pleasant function.